Monoclonal antibodies in idiopathic chronic eosinophilic pneumonia: a scoping review - Andrea Dionelly Murillo; Ana Isabel Castrillon; Carlos Daniel Serrano; Liliana Fernandez-Trujillo (BMC Pulmonary Medicine, 2024)
Abstract Background Idiopathic chronic eosinophilic pneumonia (ICEP) is a rare disease characterized by pulmonary radiological alterations, peripheral eosinophilia, and demonstrated pulmonary eosinophilia. Oral steroids (OSs) are the standard management, but relapses occur in up to 50% of patients during the decrease or suspension of steroids, usually requiring reinitiation of treatment, exposing patients to secondary events derived from the management. Management with monoclonal antibodies has been proposed in these cases to control the disease and limit the secondary effects. The objective is to describe the extent and type of evidence regarding the use of monoclonal antibodies for ICEP. Methods A panoramic review of the literature was performed. Observational and experimental studies of pediatric and adult populations that managed recurrent ICEP with monoclonal antibodies were included. Data search, selection, and extraction were performed by two independent reviewers. Results 937 studies were found. After applying the inclusion and exclusion criteria, 37 titles remained for the final analysis: a retrospective, observational, real-life study, two case series publications, and 34 case reports published in academic poster sessions and letters to the editor. In general, the use of monoclonal antibodies approved for severe asthma could be useful for the control of ICEP, since most of the results show a good response for clinical and radiological outcomes. Biological drugs seem to be a safer option for controlling relapses in ICEP, allowing lowering/suspension of OSs, and sometimes replacing them in patients intolerant to them, patients with significant comorbidities, and patients who have already developed adverse events. Conclusion The extent of the evidence supporting management of ICEP with monoclonal antibodies against IL-5 and IgE (omalizumab) is limited, but it could be promising in patients who present frequent relapses, in cortico-dependent individuals, or in patients in whom the use of steroids is contraindicated. The extent of the evidence for management with dupilumab is more limited. Studies with better design and structure are needed to evaluate quality of life and outcomes during a clear follow-up period. To our knowledge, this is the first scoping review of the literature showing the extent of the evidence for the management of ICEP with monoclonal antibodies.